A dynamic QoS provisioning model for network mobility - Noor, R.M.; Edwards, C. (2006)
This paper proposes a dynamic QoS provisioning model for network mobility. The basic idea of network mobility (NEMO) is to keep connectivity whilst the network changes its point of attachment. To achieve this, sufficient resources need to be provisioned for the entire mobile network. In our model, the packets are prioritized and classified according to the services they are subscribed to i.e. premium services or user services. Packets that are marked according to the traffic classes are then aggregated as a single request in a QoS Object in the packet header which is then sent along with the NEMO binding update message for resource reservation. QoS agents in the mobile router and access router determine whether to either send the QoS Object as a destination option or hop-by-hop option.